Deletion Polymorphism in the Angiotensin-converting Enzyme Gene as a Thrombophilic Risk Factor after Hip Arthroplasty - Philipp, Claire S.; Dilley, Anne; Saidi, Parvin; Evatt, Bruce; Austin, Harland; Zawadsky, Joseph; Harwood, David; Ellingsen, Dorothy; Barnhart, Elizabeth; Phillips, Donald J.; Hooper, William Craig (Thrombosis and Haemostasis, 1998)
Despite thromboprophylaxis, deep vein thrombosis is a common complication of major orthopedic surgery. Predisposing genetic risk factors are unknown. In this case-control study, we investigated the association of the insertion (I)/deletion (D) angiotensin converting enzyme (ACE) gene polymorphism, Factor V Leiden (R506Q) mutation, and 5,10 methylenetetrahydrofolate reductase (MTHFR) gene polymorphism with post-operative venous thrombosis in 85 patients who underwent elective total hip arthroplasty. The odds of a thrombotic event following hip surgery among subjects with the DD genotype of the ACE gene was increased more than 10-fold compared to subjects with the II genotype (odds ratio 11.7 [95% confidence interval 2.3-84.5]); it was increased 5-fold in subjects with the ID genotype compared to the II genotype (odds ratio 5.0 [95% confidence interval 1.1-34.9]). Mean plasma ACE level in control subjects not on ACE inhibitors at the time of study (n = 43) was lowest in persons homozygous for the I allele (18.9 ± 7.95 U/l), intermediate in patients with the ID genotype (31.6 ± 10.8 U/l) and highest in subjects homozygous for the D allele (44.0 ± 7.14 U/l). Mean plasma ACE level among cases was higher (33.0 U/l, n = 25) than among controls (29.4 U/l, n = 43) but this difference was not statistically significant. Neither the Factor V Leiden mutation nor MTHFR gene polymorphism increased the risk of thrombosis following hip replacement. These results demonstrate that the I/D ACE gene polymorphism is a potent risk factor for thrombosis in subjects undergoing total hip arthroplasty.